Perancangan Website Sekolah pada SMK Yapim Taruna Bandar - Santi Dewi Fadmala Naibaho; Dian Noviandri (CIVITAS: Jurnal Studi Manajemen, 2022)
Website is one of the promotional media that can be accessed online through internet networks where websites have sites that provide advertising services. Now the website has been used by many companies as one of their promotional media. Yapim Taruna Bandar High School is one of the educational institutions in Trade III, Bandar Subdistrict, Simalungun Regency that does not yet have a website or can be said to have not utilized their internet facilities. The purpose of this study was to facilitate the citizens of Yapim Taruna Bandar High School and the wider community as a means of information and promotion. Where this application has two main functions. The first is a general user, namely the website display page that contains information about Yapim Taruna Bandar High School. Then the administrator is used as data processing or can only be used by the admin.